(untitled) (Cultura Económica, 2019)
Since the decades of 1970 and 1980, with the introduction of the new models of industrial organization –electronics and information technology improvements, global markets with selective demand, flexible manufacturing and industrial democracy-, labor relationship in industry begins a transformation process, in which the human factor reaches a new dimension. Human requirements and motivation are recognized and labor is empowered. Nevertheless, it is observed that in many situations this empowerment of the human factor continues treating people as “resources”. In this work, such circumstances are analyzed and the inclusion of an integral humanistic perspective is proposed.